Fabrication of Transparent Thin Film for Application of Thin Film Transistor (TFT) and Microelectronics - Pokharel, Peshal; Shrestha, Lalita (Himalayan Journal of Science and Technology, 2022)
A thin-film transistor (TFT) is a special type of metal-oxide-semiconductor field-effect transistor (MOSFET) made by coating an insulating substrate with layers of an active semiconductor layer, metallic contacts, and the dielectric layer. FET transistors consist of three main components: source, gate, and drain. The main objective of the work is to fabricate the channel component by growing the ZnO nanostructure on the glass substrate using spin coating and spray pyrolysis methods. Thin films of zinc oxide (ZnO) were deposited on glass substrates by spin coating techniques from a precursor solution containing zinc acetate, ethanol and hydroxide of ammonia. After deposition, the films were centrifuged and evaporated. The application of spray pyrolysis has been used to deposit a wide variety of thin films, which are used in a variety of devices, such as solar cells, sensors and solid oxide fuel cells. It has been observed that the properties of the deposited thin films often depend on the preparation conditions; concentration levels of the precursor solution, coating time, electrical and optical properties of the glass substrate, etc. The average resistance of the sheet of samples F1, F5, F52, and F57 was 8.7 Ω, 9.14 Ω, 8.9 Ω and 9.42 Ω and of the samples, F2, F29, F39, and F53 were 9.5 Ω, 9.3 Ω, 9.9 Ω, 10.0 Ω respectively, at a growth temperature of 3400C. The thin films of ZnO were found to be highly transparent between the visible and near-infrared regions of the electromagnetic spectrum and the transmission of each sample decreases with three layers of ZnO seed layer. The decrease in the transmission of the samples confirms the coating of the ZnO seed layer on it. This work has demonstrated that transparent thin films can be fabricated using local techniques developed from locally available materials using less harmful chemical reagents such as zinc acetate. Such fabricated films are optically absorptive and inherently transmissive, further suggesting that they can be used as a channel material in thin film transistors.